2016
DOI: 10.1364/ao.55.002853
|View full text |Cite
|
Sign up to set email alerts
|

34  mJ Ho:YAG ceramic master oscillator and power amplifier laser at 2097  nm

Abstract: We demonstrated a 2097 nm Ho:YAG ceramic master oscillator and power amplifier system pumped by Tm:YLF lasers. Laser characteristics of 0.6 at.% and 0.4 at.% Ho:YAG ceramics were studied in CW and Q-switched modes. An output energy of 20.6 mJ at a pulse repetition frequency of 200 Hz was achieved from the master oscillator. The pulse energy was amplified to 34 mJ by the Ho:YAG ceramic amplifier with a pulse duration of 54 ns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…7) In contrast, single doped Ho 3+ media could be directly excited by readily available 1.9 µm pump sources, showing more advantages in generating higher power laser pulses. 3,8) For example, Strauss et al demonstrated an output with a pulse energy of 200 mJ and repetition rate of 50 Hz by using a Ho:YLF and Ho:LuLF slab amplifier system. 9) Ho:YAG crystal is another excellent material for 2 µm lasers due to its good thermo-mechanical properties and crystal quality.…”
mentioning
confidence: 99%
“…7) In contrast, single doped Ho 3+ media could be directly excited by readily available 1.9 µm pump sources, showing more advantages in generating higher power laser pulses. 3,8) For example, Strauss et al demonstrated an output with a pulse energy of 200 mJ and repetition rate of 50 Hz by using a Ho:YLF and Ho:LuLF slab amplifier system. 9) Ho:YAG crystal is another excellent material for 2 µm lasers due to its good thermo-mechanical properties and crystal quality.…”
mentioning
confidence: 99%